Transforming Universities for 21st Century Africa: A Case Study of Sierra Leone - JACKSON, Emerson Abraham (Journal of Research in Educational Sciences, 2024)
This study aims to examine the critical transformation necessary for universities in Sierra Leone to remain relevant in the 21st century. It focuses on aligning academic programs with the demands of the market, integrating digital tools, and fostering industry-academia collaborations. The research employs a theoretical and narrative methodology. A theoretical approach is adopted to examine academic frameworks related to curriculum reform, digital integration, and industry partnerships. A narrative methodology is used to explore practical case studies and experiences within Sierra Leone's higher education landscape. The study relies on a combination of secondary sources, including contemporary literature and policy documents, to draw relevant insights into educational transformation in Africa. The study reveals significant barriers to transformation, such as inadequate funding, misaligned curricula, and insufficient technological infrastructure. However, it also highlights key opportunities for growth, including the adoption of innovative digital tools and the reform of curricula to meet market demands. This paper provides a comprehensive analysis of Sierra Leone's higher education system, contributing to the broader discourse on university transformation in Africa. It offers actionable recommendations for policymakers and educational leaders to implement strategic reforms that align with sustainable development goals.